Static Analysis Of Bucket Wheel Dredger Upper Structure Strength Caused By Modification Of Ladder For 70 Meters Dredging Depth - Tri Saputro, Firman
Abstract Tin is one of many natural resources located across indonesian’s water. For the purpose of mining the tin, a dredger used as a tool do so. Bucket line dredger commonly used for shallow dredging. A dredger have a specific dredging depth. As the reserve of tin in the particular depth is exhausted, a dredger need to modified it’s ladder for further dredging depth. To fulfill the purpose, the dredger need to be modified into bucket wheel dredger. It has considerably smaller geometry and weight compared to the bucket wheel dredger. With this modification, the upper structure of the dredger would be able to support the weight of the ladder. If the load happens to exceed the dredger capacity, the required modification will be less than if bucket line dredger is used. This final project will use static analysis on the upper structure of the dredger that underwent modification to be able to mine at depth of 70 m. Load simulation is done using ANSYS 13.0, to understand the stress and deformation in the structure. Design criteria required a safety factor of 3. Early analysis show that the maximum stress is 177.5 MPa. This exceed the design limit. So, a modification was done by putting in additional support bar on the structure. This result in maximum stress of 80.8 MPa, and safety factor of 3.1. It can be concluded that the design is safe, according to the previously established design limit.